2003
DOI: 10.1046/j.1365-2125.2003.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the micro‐ and macro‐vascular effects of glimepiride and gliclazide in metformin‐treated patients with Type 2 diabetes: a double‐blind, crossover study

Abstract: Aims To compare the metabolic and vascular effects of two sulphonylureas (SU), gliclazide (specific for the pancreatic [SUR1] receptor) and glimepiride (a nonspecific agent that also binds to vascular and cardiac [SUR2] receptors), during chronic administration in metformin-treated patients with Type 2 diabetes (T2DM). Methods A randomized, double-blind, crossover study of gliclazide 80 mg BID and glimepiride 2 mg OD, each for 4 weeks as add-on therapy to metformin, with a 4-week washout period. Patients atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…A randomized, double-blind, crossover study of GLIC 80 mg twice daily and GLIM 2 mg once daily, each for 4 weeks as add-on therapy to metformin, found no evidence between SUR1-specific (GLIC) and nonspecific SU (GLIM) in differential effects on arterial distensibility, endothelial function, or vasodilator mechanisms. [ 102 ]…”
Section: S Ulfonylureas and C Ombinationmentioning
confidence: 99%
“…A randomized, double-blind, crossover study of GLIC 80 mg twice daily and GLIM 2 mg once daily, each for 4 weeks as add-on therapy to metformin, found no evidence between SUR1-specific (GLIC) and nonspecific SU (GLIM) in differential effects on arterial distensibility, endothelial function, or vasodilator mechanisms. [ 102 ]…”
Section: S Ulfonylureas and C Ombinationmentioning
confidence: 99%
“…This effect is not shared by other SUs, including glibenclamide, glimepiride, glipizide, and tolbutamide, as demonstrated by Jennings [18]. A recent study did not show differential effects on arterial distensibility, endothelial function, or vasodilator mechanisms in diabetic patients treated with glimepiride or gliclazide [20]; however, both groups of patients were already treated with metformin, and the effect of this drug in both groups cannot be excluded.…”
Section: Sulphonylureas' Effects On Hemorheologic and Coagulation Parmentioning
confidence: 81%
“…Studies on recombinant K-ATP channels have shown that e.g. gliclazide [68,72,73,74,75], and tolbutamide [10,14,68,76,77] inhibit Kir6.2/SUR1 currents with high affinity, but show low-affinity block of Kir6.2/SUR2 currents [12,68,73]. By contrast, glibenclamide, glimepiride, meglitinide (a molecule corresponding to the nonsulfonylurea half of glibenclamide), and repaglinide block both Kir6.2/SUR1 and Kir6.2/SUR2 channels with similar high affinity [68,69].…”
Section: Drug Binding and Interaction Sites Of Abc-transportersmentioning
confidence: 99%
“…Target # Drugname Mechanism Literature Sur1/ABCC8 (4) Ambutonium binding [88] (5) Carbutamide receptor binding [72], [89] (6) Chlorpropamide receptor binding [72], [73], [78] (7) Dexamethasone binding [90] (8) Droperidol binding [69] (9) FOXA2 binding [91], [92] (10) Glibornuride binding [93], [94], [95], [96] (11) Gliclazide binding [68], [72], [73], [74], [75] (12) Glimepiride receptor binding [68], [72], [73], [74], [79], [80] (13) Glipizide receptor binding [72], [73], [79], [80] (14) Gliquidone binding [93], [97], [98], [70], [99], [100] (15) Glisoxepide receptor binding [72], [101] (16) Glucocorticoid binding [90], [102] (17) Glyburide binding [14], [68], [76] (18) KCNJ11 binding [103] (19) Meglitinide receptor binding [72], [89] (20) Metformin receptor binding …”
Section: Inhibitorsmentioning
confidence: 99%